2010
DOI: 10.1063/1.3284954
|View full text |Cite
|
Sign up to set email alerts
|

Charge migration in Pb(Zr,Ti)O3 ceramics and its relation to ageing, hardening, and softening

Abstract: The dielectric response of hard (Fe-doped) and soft (Nb-doped) rhombohedral Pb(Zr 0.58 Ti 0.42 ) 1-x Me x O 3 (PZT; Me= Fe or Nb) ceramics was studied at subswitching conditions over a wide range of temperatures (50°C to 450 °C) and frequencies (10 mHz to 10 kHz). The results show qualitative differences in behavior of the acceptor and donor doped samples. Hard materials exhibit a steep increase of the complex permittivity with decreasing frequency. The onset of the dispersion is thermally activated with activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
92
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(97 citation statements)
references
References 65 publications
5
92
0
Order By: Relevance
“…Additional factors that can influence the S-E hysteresis of RE-BFO may be, for example, the movement of pinning centers such as charged defects during electric-field cycling 58,59 , causing internal bias fields [52][53][54][55] that can influence strain. C. High temperature piezoelectric functionality The piezoelectric coefficient (d 33 ) of the three ceramics was first evaluated as a function of the poling-electric-field (Fig.…”
Section: Bmentioning
confidence: 99%
“…Additional factors that can influence the S-E hysteresis of RE-BFO may be, for example, the movement of pinning centers such as charged defects during electric-field cycling 58,59 , causing internal bias fields [52][53][54][55] that can influence strain. C. High temperature piezoelectric functionality The piezoelectric coefficient (d 33 ) of the three ceramics was first evaluated as a function of the poling-electric-field (Fig.…”
Section: Bmentioning
confidence: 99%
“…The figure shows the reversible response going from p-type (in O 2 ) via n-type (in N 2 ) and back to p-type (in synthetic air) semiconductor behaviour. The hardness of ferroelectric PZT can be tuned by acceptor and donor substitution, 48,49 and the hardening of acceptor substituted PZT has been explained by defect ordering due to rearrangement of oxygen vacancies. 50 Such ordering has also been studied in e.g.…”
mentioning
confidence: 99%
“…Recent studies revealed that more than one process of aging may be active in one material. 8,9 Since the volume effect is related to the migration of charged carriers, both the thermodynamic and kinetic behaviors of these carriers should be considered. The crucial role played by the migration kinetics of point defects has been demonstrated in Al 3þ -doped BaTiO 3 ceramics, 10 where the Al 3þ -doping leads to lattice shrinkage and suppresses the FE aging effect at high level doping.…”
mentioning
confidence: 99%